Teaching and learning History in the time of the COVID-19 pandemic: Reflections of a senior school history teacher (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Teaching history during lockdown at an elite private school during the COVID-19 pandemic posed challenges and opportunities to draw on history and to learn new technologies. Challenges went beyond the content of history and included mental stress amongst students as a result of isolation but also empathy for victims of deepening poverty and police violence. Opportunities included international and local webinars, conferences, staff development and increased online resources.
Keywords: History; Technology; COVID-19; Poverty; Webinars; Resources